Diagnosis of an outbreak of Salmonella Typhimurium in chinchillas (Chinchilla lanigera) by pulsed-field gel electrophoresis - Gornatti Churria, Carlos Daniel (2014)
Adult chinchillas (Chinchilla lanigera) that had suddenly died in a commercial farm located in La Plata City, Buenos Aires Province, Argentina, in July 2012 were macroscopically, histopathologically, and microbiologically examined. Salmonella enterica serovar Typhimurium (S. Typhimurium) was isolated from the liver, spleen, heart, lungs, kidneys and intestines from each of the five animals evaluated. The five strains were susceptible to ampicillin, cephalotin, cefotaxime, nalidixic acid, gentamicin, streptomycin, chloramphenicol, fosfomycin, nitrofurantoin and trimethoprimsulfamethoxazole, and resistant to tetracycline. Each of the five S. Typhimurium isolates was analyzed by XbaI-pulsed-field gel electrophoresis (PFGE), showing an identical electrophoretic profile with 15 defined bands, which was found to be identical to pattern ARJPXX01.0220 of the PulseNet Argentine National database of Salmonella PFGE patterns. This is the first work describing the postmortem diagnosis of an outbreak of salmonellosis in chinchillas by using molecular methods such as PFGE.